Exploring staff attitudes to routine HIV testing in non-traditional settings: a qualitative study in four healthcare facilities. Issue 8 (6th July 2012) - Thornton, Alicia Claire; Rayment, Michael; Elam, Gillian; Atkins, Mark; Jones, Rachel; Nardone, Anthony; Roberts, Patrick; Tenant-Flowers, Melinda; Anderson, Jane; Sullivan, Ann Kathleen; ,
Abstract : Objectives: To explore staff attitudes towards and experiences of the implementation of routine HIV testing in four healthcare settings in areas of high diagnosed HIV prevalence. Methods: As part of the HINTS (HIV Testing in Non-traditional Settings) Study, routine offer of an HIV test to all 16–65-year-old patients was conducted for 3 months in an emergency department, an acute admissions unit, a dermatology outpatients department and a primary care practice. The authors conducted focus groups with staff at these sites before and after the implementation of testing. Transcriptions of focus groups were subject to thematic analysis. Results: Four major themes were identified: the stigma of HIV and exceptionalisation of HIV testing as a condition; the use of routine testing compared with a targeted strategy as a means of improving the acceptability of testing; the need for an additional skill set to conduct HIV testing; and the existence within these particular settings of operational barriers to the implementation of HIV testing. Specifically, the time taken to conduct testing and management of results were seen by staff as barriers. There was a clear change in staff perception before and after implementation of testing as staff became aware of the high level of patient acceptability. Conclusions: The routine offer of HIV testing in general medical services is feasible, but implementation requires training and support for staff, which may be best provided by the local sexual health service.